Hubungan Antara Kematangan Emosi dengan Agresi Pada Remaja di SMK Negeri Padang - Dewi Aisyah Fajar; Linda Fitria; Yuliawati Yunus (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
Emotional instability over time, attempts to adjust behavior from previous phases of development, feeling as if "lost", and fluctuating emotions often fill the daily life of adolescents. This causes teenagers to always look for quick methods to vent their emotions without considering the consequences of their actions. Aggression is not a behavior dominated by a group of people alone, in each person there is an urge to aggression. Aggression can vary, depending on how a person responds to the stimulus that comes to him. This research only focused to determine the relationship between emotional maturity and aggression in class x adolescents at SMK Negeri 9 Padang even semester of the 2022/2023 school year. The type of research used is quantitative method. The study population amounted to 424 people enrolled in the 2022/2023 school year, with a sample of 206 people taken using proportional rondom sampling technique. This research examines the relationship between emotional maturity and aggression. The instrument used in data collection in this study was a questionnaire prepared according to the Likert scale model. Data analysis was carried out using a statistical program on the SPSS 24 computer and Microsoft Excel. Based on the results of the hypothesis the rcount value is 0.473 while the rtable value is 0.1367 because the value of r count is greater than r table (0,473> 0,1367), there is a significant positive relationship between emotions and aggression in class x adolescents in SMK Negeri 9 Padang.